A global analysis of archaeal transcription reveals two modes of Spt4/5 recruitment to the RNA polymerase - Smollett, Katherine (Nat Microbiol, 2017)
The archaeal transcription apparatus is closely related to the eukaryotic RNA polymerase (RNAP) II system, while archaeal genomes are more similar to bacteria with densely packed genes organised in operons. This makes understanding transcription in archaea vital, both in terms of molecular mechanisms and evolution. Very little is known about how archaeal cells orchestrate transcription on a systems level. We have characterised the genome-wide occupancy of the Methanocaldococcus jannaschii transcription machinery and its transcriptome. Our data reveal how the TATA and BRE promoter elements facilitate the recruitment of the essential initiation factors TBP and TFB, respectively, which in turn are responsible for the loading of RNAP into the transcription units. The occupancy of RNAP and Spt4/5 strongly correlate with each other and with the RNA levels. Our results show that Spt4/5 is a general elongation factor in archaea since its presence on all genes matches RNAP. Spt4/5 is recruited proximal to the TSS on the majority of transcription units, while on a subset of genes including rRNA and CRISPR loci, Spt4/5 is recruited to the transcription elongation complex during early elongation within 500 bp of the TSS, and akin to its bacterial homolog NusG.